Management of infection by the Zika virus - Falcao, Melissa Barreto (2016)
A panel of national experts was convened by the Brazilian Infectious Diseases Society in order to organize the national recommendations for the management of zika virus infection. The focus of this document is the diagnosis, both clinical and laboratorial, and appropriate treatment of the diverse manifestations of this infection, ranging from acute mild disease to Guillain-Barré syndrome and also microcephaly and congenital malformations.